2017
DOI: 10.1093/geront/gnx009
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Elderspeak: A Qualitative Study of Three Alternatives

Abstract: These 3 communicative strategies offer examples of lexically and grammatically complex ways to communicate with older adults who have little other opportunity for similarly complex interaction and may reduce resistiveness to care, and linguistic isolation, which has been linked to cognitive decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Stans, Dalemans, de Witte, and Beurskens () reported that it is essential to be aware of the illnesses experienced by older adults and how they influence communication. Communications with cognitively or physically affected older adults can be facilitated using blessings, jokes and narratives (Corwin, ), while good alternatives to verbal communication are the use of body language or involving family members in interactions with older adults (Forsgren et al., ). The participants in this study perceived that difficulty communicating with older adults was mainly due to their lack of competence in geriatric care, and this self‐blaming often increased the turnover rate at facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Stans, Dalemans, de Witte, and Beurskens () reported that it is essential to be aware of the illnesses experienced by older adults and how they influence communication. Communications with cognitively or physically affected older adults can be facilitated using blessings, jokes and narratives (Corwin, ), while good alternatives to verbal communication are the use of body language or involving family members in interactions with older adults (Forsgren et al., ). The participants in this study perceived that difficulty communicating with older adults was mainly due to their lack of competence in geriatric care, and this self‐blaming often increased the turnover rate at facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Contextual factors, including environmental factors and dyadic characteristics, may also serve as antecedents to elderspeak. For example, convents were found to have extremely low rates of elderspeak, leading to the hypothesis that elderspeak depends on the culture of the community ( Corwin, 2017 ). Somewhat unexpectedly, however, nursing home residents did not report receiving more elderspeak than cognitively intact older adults residing in the community ( O’Connor & Rigby, 1996 ).…”
Section: Resultsmentioning
confidence: 99%
“…Such health promotion pratices contribute to the engagement of the aged in richer communicative interactions with their interlocutors and can contribute to the reduction of linguistic isolation and its consequences, including the cognition of this group. 24 Additionally, this professional can contribute to the identification of changes in language skills in individuals at risk for MCI. 7 The present study has several limitations.…”
Section: Discussionmentioning
confidence: 99%